Finasteride inhibits melanogenesis through regulation of the adenylate cyclase in melanocytes and melanoma cells - Seo, Jae Ok; Yumnam, Silvia; Jeong, Kwang Won; Kim, Sun Yeou (Archives of pharmacal research, 2018)
Finasteride is a well-known 5α-reductase inhibitor used for treatment of alopecia and prostate cancer. But the effect of finasteride in regulating melanogenesis is still unclear. In the present study the role of finasteride on melanogenesis was investigated. Finasteride decrease melanin level in melanocyte melan-a cells and B16F10 melanoma cells without inducing cytotoxicity. MC1R (melanocortin 1 receptor) protein expression was also inhibited by finasteride thereby decreasing the expression of adenylate cyclase, MITF (Melanogenesis associated transcription factor), tyrosinases, TRP (tyrosinase-related protein) -1 and -2. Thus our study suggest that finasteride inhibits melanogenesis in melanocyte and melanoma cells by inhibiting MC1R.